1994
DOI: 10.1002/hep.1840190619
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia-induced brain edema and intracranial hypertension in rats after portacaval anastomosis

Abstract: Brain edema, leading to intracranial hypertension and brain herniation, is a major cause of death in fulminant liver failure. Astrocyte swelling is a prominent neuropathological feature in experimental fulminant liver failure. It has been postulated that the osmotic effects of glutamine, generated in astrocytes from ammonia and glutamate in a reaction catalyzed by glutamine synthetase, could mediate brain swelling. Normal rats and rats that received a portacaval anastomosis were infused with ammonium acetate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
3

Year Published

1998
1998
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 225 publications
(83 citation statements)
references
References 27 publications
3
77
3
Order By: Relevance
“…This finding is in full accordance with the literature where data showed that only plasma concentrations of ammonia above $2 mmol/L are associated with increased ICP and CBF in naïve rats [18]. Moreover, in rats with portacaval anastomosis and a plasma ammonia concentration maintained close to 1 mmol/L, ICP and CBF start to increase after more than 150 min [19][20][21][22][23], a much more protracted delay than that we observed in rats with moderate hyperammonemia and given LPS.…”
Section: Main Findingssupporting
confidence: 94%
“…This finding is in full accordance with the literature where data showed that only plasma concentrations of ammonia above $2 mmol/L are associated with increased ICP and CBF in naïve rats [18]. Moreover, in rats with portacaval anastomosis and a plasma ammonia concentration maintained close to 1 mmol/L, ICP and CBF start to increase after more than 150 min [19][20][21][22][23], a much more protracted delay than that we observed in rats with moderate hyperammonemia and given LPS.…”
Section: Main Findingssupporting
confidence: 94%
“…This may have important implications in hyperammonemic syndromes such as Hepatic Encephalopathy (HE) due to ALF. The principal cause of mortality in HE is brain edema, leading to increased intracranial pressure and subsequently brain herniation (40,41). It has been suggested for long that astrocyte swelling due to the increased intracellular osmolarity by glutamine accumulation is the major reason responsible for brain edema in HE due to ALF.…”
Section: Discussionmentioning
confidence: 99%
“…Ammonia related brain edema is possibly the first event [51]. CBF autoregulation is lost in patients with ALF resulting in cerebral hyperemia [40,52].…”
Section: Intracranial Hypertension: Pathophysiologic Basis and Managementioning
confidence: 99%